\(x^3+y^3+z^3+6=3\left(x^2+y^2+z^2\right)\Rightarrow\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-xz\right)+3xyz+6=3\left(x^2+y^2+z^2\right)\)Mà x+y+z=3
\(\Rightarrow3\left(x^2+y^2+z^2-xy-xz-yz\right)+3xyz+6=3\left(x^2+y^2+z^2\right)\)
\(\Rightarrow x^2+y^2+z^2-xy-yz-xz+xyz+2=x^2+y^2+z^2\)
\(\Rightarrow xyz-xy-yz-xz+2=0\Rightarrow\left(xyz-xy\right)-\left(yz-y\right)-\left(xz-x\right)+\left(2-x-y\right)=0\)
\(\Rightarrow xy\left(z-1\right)-y\left(z-1\right)-x\left(z-1\right)+\left(2-3+z\right)=0\Rightarrow xy\left(z-1\right)-y\left(z-1\right)-x\left(z-1\right)+\left(z-1\right)=0\)
\(\Rightarrow\left(z-1\right)\left(xy-x-y+1\right)=0\Rightarrow\left(z-1\right)\left[\left(xy-x\right)-\left(y-1\right)\right]=0\Rightarrow\left(z-1\right)\left[x\left(y-1\right)-\left(y-1\right)\right]=0\)
\(\Rightarrow\left(z-1\right)\left(x-1\right)\left(y-1\right)=0\)
Suy ra có ít nhất 1 trong 3 số x,y,z bằng 1,khi đó A=0
Vậy A=0